Surveillance of anthelmintic treatments on ruminant farms to detect resistance in a low-prevalence area - Rosa D’Ambrosio; Loredana Baldi; Stefania Cavallo; Alessandro Nappa; Luigia Di Donato; Roberta Brunetti; Mirella Santaniello; Antonella Pesce; Marialuisa Buonanno; Laura Rinaldi; Antonio Bosco (BMC Veterinary Research)
Abstract Background Difficulty in combating gastrointestinal nematode (GIN) infection in ruminants is increasing worldwide, owing to progressive anthelmintic resistance (AR). This study evaluates the AR current status against benzimidazoles and macrocyclic lactones on 20 sheep and 10 cattle farms in southern Italy that have performed a greater number of anthelmintic treatments in recent years. On each farm, the animals were randomly divided into two groups of 20 animals; one group was treated with ivermectin (IVM, 0.2 mg/kg of body weight), and the other with albendazole (ALB, 3.8 mg/kg of body weight). In each farm, an individual faecal egg count was performed on samples collected on the day of treatment (D0) and after 14 days (D14) using the Mini-FLOTAC technique. For each group, coprocultures were performed on D0 and D14. An in vitro test (egg hatch assay—EHA) and a follow-up FECR test with fenbendazole were performed to confirm the low in vivo efficacy. To better understand farm management and the anthelmintic treatment methods commonly adopted, a questionnaire was formulated and submitted to farmers during the recruitment phase. The content of the questionnaire was identical for cattle and sheep. Results The in vivo test (FECR) showed a high efficacy (from 96.7% to 100%) for both tested anthelmintics in all cattle farms and in 18 sheep farms. A low efficacy for ALB has been detected in two sheep farms, with FECR value of 86.0% for Farm 1 and 92.4% for Farm 2 with predominant GIN genera of Trichostrongylus and Haemonchus on post-treatment samples. The EHA confirmed AR on both sheep farms with low efficacy in Farm 1 of 87.0% and in Farm 2 of 77.0%. At the end of the administration period, questionnaires were collected and a descriptive analysis of data was carried out. Cattle farmers displayed a low perception of the AR problem, while sheep farmers had a higher perception. Conclusions The phenomenon of AR in low-prevalence areas certainly needs to be monitored on each farm in conjunction with the usual anthelmintic treatments, so as to be able to promptly identify and solve the problem.